Bacterial sexually transmitted infections. (28th March 2019) - Buder, Susanne; Schöfer, Helmut; Meyer, Thomas; Bremer, Viviane; Kohl, Peter K.; Skaletz‐Rorowski, Adriane; Brockmeyer, Norbert
Summary: Worldwide, the incidence of bacterial sexually transmitted infections (STIs) has shown a significant increase in recent years. In Germany, this circumstance is reflected by a rise in the number of reported syphilis cases. There has also been an uptick in the incidence of non‐notifiable STIs such as gonorrhea and infections caused by Chlamydia trachomatis and Mycoplasma genitalium . A key factor in the spread of these infections is their varied clinical presentation, which includes urogenital, pharyngeal and rectal involvement as well as a large number of asymptomatic cases. New real‐time multiplex PCR methods allow for rapid and targeted detection of STI pathogens. The most common bacterial STI is urogenital chlamydial infection caused by serovars D–K, which affects young adults in particular. Lymphogranuloma venereum (LGV) caused by L serovars often presents as chlamydial proctitis. In recent years, Neisseria (N.) gonorrhoeae has shown a significant development of resistance, with high‐level monoresistance and multiresistance to antibiotics commonly used for treatment. It is therefore imperative that sensitivity testing of N. gonorrhoeae be performed in addition to nucleic acid amplification tests (NAATs). Increased drug resistance has also been observed for Mycoplasma genitalium, a fact that complicates treatment.